Efektivitas Leaflet dalam Meningkatkan Pengetahuan Hipertensi pada Lansia di Desa Gandatapa - Kusuma, Ikhwan Yuda; Nawangsari, Desi; Prabandari, Rani; Kurniasih, Khamdiyah Indah; Fauziah, Fauziah; Abely, Nastasya Anis; Safitri, Cindy Ade (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction:  Hypertension is a significant global health issue that often presents without symptoms, leaving many individuals unaware of their condition. Effective management and prevention of hypertension require increased awareness and education, particularly among the elderly population, who are at higher risk. Objective: This study aims to evaluate the effectiveness of health counseling using leaflets in improving hypertension knowledge among the elderly at Integrated service post (Posyandu) community association (RW) 4 Gandatapa. Method: This descriptive quantitative study employed a pre-post design. Health counseling was conducted using leaflets at  Integrated service post  (Posyandu) community association (RW) 4 Gandatapa on July 16, 2024, involving 44 elderly participants aged 65-70 years. Knowledge levels were assessed using pre-test and post-test questionnaires. The intervention included distributing leaflets and conducting a discussion session to reinforce the information provided. Result:The study observed a significant increase in participants' knowledge about hypertension, with average knowledge scores rising from 43% in the pre-test to 63% in the post-test. Conclusion: The findings suggest that health counseling using leaflets is an effective method for improving hypertension knowledge among the elderly. However, to optimize the impact, future interventions should consider additional support methods, especially for those with limited literacy or visual impairments.